The Association Between Daily Step Count, Step Frequency and the Risk of Chronic Obstructive Pulmonary Disease: A Cross-Sectional Study Using NHANES Data - Yuan L; Tian Z; Jia X; Chen Z (International Journal of COPD, 2025)
Lindong Yuan,1,2 Zhen Tian,3 Xiaodong Jia,3 Zhe Chen4 1Department of Respiratory and Critical Care Medicine, Tianjin Medical University General Hospital, Tianjin, People’s Republic of China; 2Department of Respiratory and Critical Care Medicine, Liaocheng People’s Hospital, Liaocheng, Shandong Province, People’s Republic of China; 3Joint Laboratory for Translational Medicine Research,Liaocheng People’s Hospital, Liaocheng, Shandong Province, People’s Republic of China; 4Department of Geriatrics,Tianjin Geriatrics Institute,Tianjin Medical University General Hospital, Tianjin, People’s Republic of ChinaCorrespondence: Zhe Chen, Tianjin Medical University General Hospital, No. 154 Anshan Road, Heping District, Tianjin, 300052, People’s Republic of China, Email gh_tjzyy2020@163.comBackground: Chronic obstructive pulmonary disease (COPD) is a major public health concern globally, and physical activity is considered a modifiable factor in its prevention.Purpose: This study examined the association between daily step count, step frequency, and the prevalence of chronic obstructive pulmonary disease (COPD) using nationally representative data.Patients and Methods: A cross-sectional analysis was conducted using data from adults aged ≥ 40 years in the 2003– 2006 National Health and Nutrition Examination Survey (NHANES). Participants wore accelerometers for 7 days to measure daily step count and three step frequency indicators: bout cadence, peak 30-minute cadence, and peak 1-minute cadence (steps/minute). Weighted logistic regression was used to assess associations with COPD, adjusting for demographic, behavioral, and health-related covariates. Sensitivity analyses and subgroup analyses were conducted to confirm robustness.Results: Among 3690 participants (representing ~26.8 million US adults), higher daily step count and step frequency were inversely associated with COPD prevalence. Compared to those taking < 4000 steps/day, those taking ≥ 8000 steps/day had a 63% lower odds of COPD (OR 0.37, 95% CI 0.15– 0.91; P for trend < 0.001). Higher bout cadence (92.3– 153.4 steps/minute) and peak 30-minute cadence (69.8– 128.2 steps/minute) were also associated with significantly reduced COPD odds (ORs 0.30 and 0.33, respectively). Combined higher step count and frequency yielded a greater risk reduction. Restricted cubic splines indicated a nonlinear association, and ROC analysis showed moderate discriminatory power (AUC 0.71– 0.75). Results remained robust in sensitivity analyses and across subgroups.Conclusion: In this cross-sectional study of US adults, higher daily step counts and greater walking cadence were associated with a lower prevalence of COPD. These findings support the relevance of step-based metrics in assessing COPD risk, although longitudinal studies are needed to establish causality.Keywords: chronic obstructive pulmonary disease, NHANES database, physical activity, step count, step frequency